2005
DOI: 10.1099/vir.0.80724-0
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of epidermal growth factor receptor complex formation and Ras signalling in cells harbouring the hepatitis C virus subgenomic replicon

Abstract: Hepatitis C virus non-structural NS5A protein inhibits epidermal growth factor (EGF)-stimulated activation of the Ras-ERK mitogen-activated protein kinase pathway at a point upstream of Ras activation. To determine the mechanism of this inhibition, the events occurring between the EGF receptor and Ras in Huh-7 cells harbouring the HCV subgenomic replicon were investigated. It was shown that, following EGF stimulation, these cells exhibited decreased EGF receptor tyrosine phosphorylation, aberrant recruitment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…Previous studies have demonstrated the ability of NS5A of genotype 1 HCV to inhibit signalling of the Ras-Erk pathway (Georgopoulou et al, 2003;Macdonald et al, 2003Macdonald et al, , 2005aTan et al, 1999); our data show that this ability is conserved by NS5A from the genotype 2a JFH-1 isolate, consistent with the absolute conservation of the class II polyproline motif (PP2) throughout all HCV isolates. Furthermore, this inhibition occurs within the first 24 h p.t., suggesting it is required in the early stages of the viral life cycle.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have demonstrated the ability of NS5A of genotype 1 HCV to inhibit signalling of the Ras-Erk pathway (Georgopoulou et al, 2003;Macdonald et al, 2003Macdonald et al, , 2005aTan et al, 1999); our data show that this ability is conserved by NS5A from the genotype 2a JFH-1 isolate, consistent with the absolute conservation of the class II polyproline motif (PP2) throughout all HCV isolates. Furthermore, this inhibition occurs within the first 24 h p.t., suggesting it is required in the early stages of the viral life cycle.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously shown that NS5A of HCV genotype 1 inhibited Ras-Erk signalling, either when expressed alone or in the context of a culture-adapted subgenomic replicon or full-length HCV expression construct (Macdonald et al, 2003(Macdonald et al, , 2005aMankouri et al, 2008). To test the effects of the Ras-Erk pathway on HCV RNA replication we chose to use the recently developed genotype 2a-based transient luciferase replicon SGR-luc-JFH-1 (Targett- Adams & McLauchlan, 2005), because this replicon (unlike the genotype 1b versions) demonstrated high levels of replication within a short timescale (,24 h), which would allow quantitative measurement of viral RNA replication in the presence of inhibitors of Ras-Erk signalling.…”
Section: Perturbation Of Ras-erk Signalling Occurs In the Context Of mentioning
confidence: 99%
“…Fewer studies have demonstrated a negative correlation between ERK activity and viral protein expression such as we have described. One such study demonstrated that the hepatitis C virus nonstructural NS5A protein inhibits EGF-stimulated activation of the ERK pathway by inhibiting EGFR complex formation (27). A recent study by Yoshizuka et al reported that the expression of the HIV type 1 (HIV-1) Vpr protein is associated with the downregulation of genes in the ERK/ MAPK pathway and with decreased phosphorylation of ERK1/2 (49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by our group (Macdonald et al, 2003(Macdonald et al, , 2005a and others (Georgopoulou et al, 2003) has shown that NS5A, when expressed either alone or in the context of the complete polyprotein, is able to block Ras-Erkpathway-mediated activation of the AP-1 transcription factor in a manner that was dependent on the presence of a conserved C-terminal polyproline motif (consensus sequence PxxPxR) within NS5A. As GBV-B NS5A lacks this PxxPxR motif we predicted that GBV-B NS5A would be unable to modulate this mitogenic signalling cascade.…”
Section: Gbv-b Ns5a Does Not Inhibit Activation Of the Ap-1 Transcripmentioning
confidence: 99%
“…In addition NS5A has been shown to bind to and modulate a range of cellular proteins, influencing activation of signalling pathways . Of particular interest is the observation that NS5A inhibits the Ras-Erk mitogen-activated protein kinase (MAPK) pathway acting between the epidermal growth factor receptor (EGFR) and the activation of Ras (Georgopoulou et al, 2003;Macdonald et al, 2003Macdonald et al, , 2005aTan et al, 1999). Furthermore, NS5A has also been shown to bind to, and activate, phosphoinositide 3-kinase (PI3K), resulting in activation of the downstream effector serine/ threonine kinase Akt/protein kinase B (He et al, 2002;Street et al, 2004) and elevating b-catenin-dependent transcription (Street et al, 2005).…”
Section: Introductionmentioning
confidence: 99%